CONTROLLED-RELEASE FERTILIZATION ON THE ANGICO-BRANCO INITIAL GROWTH - BRONDANI, Gilvano Ebling; SILVA, Ariadne Josiane Castoldi; REGO, Suelen Santos; GRISI, Fernanda Almeida; NOGUEIRA, Antonio Carlos; WENDLING, Ivar; ARAUJO, Marla Alessandra de (Scientia Agraria, 2008)
The use of controlled-release fertilizer is one among the most modern techniques utilized in seedlings production systems, on other hand there are few reports about its effects on the growth characteristics in native trees. This work aimed to test increasing doses of controlled-release fertilizer on the initial growth of Anadenanthera colubrina seedlings. The seeds were planted in small size plastic tubes (110 cm3), which contained pínus bark and vermiculite as substratum base. The experiment was conducted in the whole randomized delineation in split-plot in time arrangement, where the levels were six Osmocote® doses (control, 1000, 2000, 3000, 4000 e 5000 mg dm-3), and five evaluation times (0 - germination instant, 15, 35, 65 and 95 days). For each time, were evaluated the growth characteristics: height; leaves number; nodes number; stem diameter; height/diameter relation; root system total length; root volume and root, stem, leave, shoot and total dry matter. During the 95 days, the tested fertilization influenced the majority of growth characteristics. The greater medium values of the seedlings growth characteristics: leaves number, stem diameter and dry matter; were observed in fertilizer doses around 2000 mg dm-3. The greater height occurred in 2743 mg dm-3 dose, and height/diameter relation to 3544 mg dm-3 dose. However, the characteristics root system total length and root volume presented a negative response to the fertilization system utilized.